Vloga matičnih celic pri napredovanju in zdravljenju glioma - Obrez, Mateja (Zdravniški vestnik, 2013)
The concepts of tumour origin and stochastic nature of carcinogenesis are being challenged today by hierarchical models that predict the existence of cancer stem cells (CSCs), which are postulated as unique cell population capable of infinite self renewal, multilineage differentiation and having a higher resistance to conventional cancer therapy thus facilitating malignant growth and therapy resistance. Accordingly, successful treatment of adult brain tumourglioma and its most malignant stageglioblastoma multiforme (GBM), would require the elimination of CSCs to avoid tumour relapse. Yet, with available therapy (i.e. surgery) in GBMs this cannot be achieved, due to infiltrative growth of a subpopluation of GBM cells with highly expressed migratory genes (migratome) into the normal brain tissue. Besides CSCs a proven prerequisite for tumour development and progression, tumour bulk mass also comprises haematopoietic stem cells, endothelial progenitor cells and mesenchymal stem cells (MSCs). The role of these other types of stem cell was shown to largely depend on the tumour microenvironment, where their contradictory anti-tumour action was evidenced. Yet, the exact mechanisms and MSCs role in cell-mediated modulation of tumour behaviour via paracrine and direct interactions with GBM (stem) cells still remain unknown. Nevertheless these stem cells, particularly MSCs, may represent novel therapeutic vectors for enhanced target-site delivery of chemotherapeutics, which are urgently needed to improve efficiency of current glioma treatment. So far, cell therapy using MSCs appears promising, due to MSCs selective tumour tropism and their immuno-modulatory potential regarding treatment of GBM, which will be discussed in this review.
Keywords: celična terapija; cell therapy; glioblastoma multiformae; gliom; matične celice; mesenchymal stem cells; mezenhimske matične celice; tumorji; tumorske matične celice; tumour micro-environment; tumour stem cells